2009
DOI: 10.1177/070674370905400704
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia: A Syndrome Appears, Disappears, and is Rediscovered

Abstract: Highlights • Catatonia is the psychiatric syndrome of disturbed motor functions amid disturbances in mood and thought. • It is identified by symptom clusters, verified by the acute relief afforded by barbiturates or benzodiazepines, and validated by the remission with these agents and with ECT. • Catatonia is inappropriately identified as a type of schizophrenia in the psychiatric classification. It is more often found in patients with mania, depression, systemic medical illnesses, and neurotoxicity. It deserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 34 publications
(31 reference statements)
0
55
0
5
Order By: Relevance
“…Our results lend support to the hypothesis that catatonic schizophrenia might be biologically distinct from other types of schizophrenia, as previously suggested. 1,[4][5][6] More tenuous is the finding that catatonic schizophrenia may have a stronger relationship to maternal ageing and/or to mental illness in the father compared with other schizophrenia. Prior reports on catatonic schizophrenia have been limited to cross sectional and case control studies, and case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results lend support to the hypothesis that catatonic schizophrenia might be biologically distinct from other types of schizophrenia, as previously suggested. 1,[4][5][6] More tenuous is the finding that catatonic schizophrenia may have a stronger relationship to maternal ageing and/or to mental illness in the father compared with other schizophrenia. Prior reports on catatonic schizophrenia have been limited to cross sectional and case control studies, and case series.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In the past several decades, however, the many descriptions of catatonia as a syndrome in patients with mood disorders, medical disorders, and toxicities have put the syndrome in a new light. Some authors argue that catatonia should be considered as a separate syndrome, 1,[4][5][6] or not exclusively as a subtype of chronicschizophrenia, 4 pointingoutthat catatoniapresents more frequently in psychiatric inpatients diagnosed with mood disorders than in those with schizophrenia. 2 Catatonic symptoms also co-occur with other psychiatric diseases and with general medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although catatonia is more commonly found among patients with schizophrenia, it is also seen in patients with mania, depression and systemic medical illnesses (7). The presentation and the course of symptoms in this patient, suggest early onset schizophrenia.…”
Section: Discussionmentioning
confidence: 67%
“…The literature suggests that acute relief from catatonia can be achieved by benzodiazepines or with electro convulsive therapy (7). In this case, clonazepam was used due to availability, although most reports suggest lorazepam as the first line of treatment in this age group (8).…”
Section: Discussionmentioning
confidence: 99%
“…42 Catatonia is common among chronically ill psychotic patients, but is more frequent in patients with mood disorders. [43][44][45] In pediatric populations, catatonia is reported among those with mental retardation and autistic spectrum disorder. 46,47 Recently, it was shown that most, if not all, patients with anti-N-methyl-D-aspartate-receptor encephalitis present with catatonic symptoms.…”
Section: Catatoniamentioning
confidence: 99%